Unraveling Anemia in Young Children: Insights from Western Côte d’Ivoire - Mocket Adolphe Ehouman; Kouakou Eliezer N`Goran; Ahossan André Ehouman; Pamela Nassinata Dosso (Recent Updates in Disease and Health Research Vol. 2, 2024)
Background: Anemia is a major public health problem affecting nearly a quarter of the world’s population. The global prevalence of anemia was 39.8% in children aged 6 to 59 months and 29.9% in women of childbearing age. Very commonly in the subtropics, helminthes or malaria co-infects the same person, causing morbidities that vary according to age and region. This research study aims to characterize the type of anemia observed in <7 years old children in Western Côte d`Ivoire in order to recommend a better strategy of care. Methods: The study was carried out from March 2020 to May 2021 in 22 villages of the “Tonkpi Region” (Man). It involved 451 children; boys and girls aged 3 months to 6 years who provided venous blood samples that were subjected to a FBC for the diagnosis and characterization of anemia. The data were analysed by using SPSS and STATA. Univariate analysis (Chi-2 test (x2) and P: (Probability) were used for comparison between groups. Significant test was considered at a threshold of 0.05. Results: Among 451 selected children who completed the study, 221(49.0%) were girls and 230(51.0 %) were boys. The prevalence of anemia was 248 (55.0%) of which 76(30.7%) was mild, 164(66.1%) moderate and 8(3.2%) severe. Its characterization showed the predominance of hypochromic microcytic anemia (HMA) with 195(78.63%) followed by normochromic microcytic anemia 29(11.69%), normochromic normocytic anemia 14(5.65%) and lastly, hypochromic normocytic anemia 10(4.03%). The findings revealed that both genders are equally affected though Children aged 3 months-2 years are slightly more affected compared to older children (3 to 6 years). Conclusion: The prevalence of anemia is high with moderate anemia and HMA being more prevalent in children <7 years of which 30.7% mild, 66.1% moderate and 3.2% severe. Infants \(\)2 years and the children \(\)5 years were the most affected at a prevalence of 66.0% and 51.5% respectively.